2022
DOI: 10.1007/s00345-022-04036-w
|View full text |Cite|
|
Sign up to set email alerts
|

Extract from Cucurbita pepo improves BPH symptoms without affecting sexual function: a 24-month noninterventional study

Abstract: Purpose To assess the symptoms, quality of life and sexual well-being in patients with lower urinary tract symptoms due to benign prostatic hyperplasia LUTS/BPH treated with pumpkin seed soft extract (PSE) in routine practice. Methods This noninterventional study included 130 men treated for up to 24 months. The International Prostate Symptom Score (IPSS) and related quality of life, Aging Males’ Symptoms Scale (AMS), and International Index of Erectile Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, further studies are needed to provide scientific evidence. [ 25 26 ]. Limitations of this study are that the duration of treatment was short by 12 weeks, the prostate size was not measured and urodynamic study was not performed in consideration of patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to provide scientific evidence. [ 25 26 ]. Limitations of this study are that the duration of treatment was short by 12 weeks, the prostate size was not measured and urodynamic study was not performed in consideration of patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Theil et al in a 24-month clinical study of 83 men (mean age 65.2 ± 8.7 years) with moderate LUTS/BPH symptoms, showed that pumpkin seed extract (500 mg capsules) taken twice per day significantly improved IPSS levels after 12 and 24 months in over 50% of the subjects [ 143 ]. The proportion of patients with QOL scores at baseline (mostly satisfied) was 11 percent that rose to 62 percent and 73 percent at 12 and 24 months, respectively.…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%
“…The proportion of patients with QOL scores at baseline (mostly satisfied) was 11 percent that rose to 62 percent and 73 percent at 12 and 24 months, respectively. No adverse events were reported, and the AMS and International Index of Erectile Function (HEF-5) scores indicated no negative impact on function during the treatment interval [ 143 ]. The authors concluded that pumpkin seed extract provided significant relief in men with moderate LUTS/BPH symptoms without side effects.…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%